AKTUALISASI NILAI PANCASILA SEBAGAI UPAYA MEMBANGUN KARAKTER REMAJA DI DESA KERTONATAN KECAMATAN KARTASURA PADA PASCA MASA PANDEMI COVID-19 - Suyahman, Suyahman (Academy of Education Journal, 2023)
The existence of Pancasila values in the life of the nation and state becomes a frame of reference for the attitudes, behaviors and deeds of all citizens without exception. The fact is that many attitudes, behaviors, and deeds are found that do not reflect the values of Pancasila. Such conditions cause the atmosphere of national and state life to be less conducive. If this is left unchecked, it can threaten the existence of Pancasila as the ideology and basis of the Indonesian state. Therefore, it is necessary to multiply scientific studies to find a solution. That's why this research was carried out with the title Actualization of Pancasila Values as an effort to build the character of adolescents in Kertonatan Village, Kartasura District in the aftermath of the COVID-19 pandemic. This research was conducted in the post-COVID-19 pandemic period, meaning that it was carried out after community members were less actualized, so that many attitudes, behaviors, and actions were found that were not in accordance with the values of Pancasila. If this is left unchecked, it can be a threat to the sustainability of Pancasila, therefore a solution must be found so that the value of Pancasila remains the foundation in building the character of the nation's children. In line with this phenomenon, the main problem was formulated: How to actualize the value of pancasila as an effort to build the character of adolescents in Wirogunan village during the Covid-19 pandemic? The purpose of his research is to describe the process of actualizing the value of pancasila as an effort to build the character of adolescents in Wirogunan village. The type of research is qualitative research with a case study approach, the source of the data; Teenagers, parents, community leaders, religious leaders and youth leaders in Wirogunan Village, the object is the actualization of Pancasila values, and the character of adolescents. Data collection methods: observation, interview and documentation. Data analysis techniques Interactive techniques consist of 3 steps: data reduction, data display, data verification. Research results: based on field observations, interviews and documentation, it was found that the attitudes, behaviors, and deeds of adolescents in Wirogunan Village did not reflect the value of Pancasila as a basis for building adolescent character. The conclusion: actualizing the value of Pancasila as an effort to build RMA's character is less than optimal, it needs to be done intensively, continuously and continuously.